PERAN DUKUN BAYI DALAM PENANGANAN KESEHATAN IBU DAN ANAK DI DESA BOLO KECAMATAN DEMAK KABUPATEN DEMAK (Solidarity: Journal of Education, Society and Culture, 2013)
Role of traditional birth attendants are still very great influence in society. Similarly, the village of Bolo is still using the services of traditional birth attendants in maternal and child health care. Interestingly, although traditional birth attendants in the village of Bolo as a second reference chosen by the public, but public confidence in health care that will be done by traditional birth attendants are still strong. This study aims to determine what role that is run by midwives and traditional birth attendants cause still has an important role in the village of Bolo. This study uses qualitative methods, with in-depth interview technique, participant observation and documentation. Research subjects are traditional birth attendants, while the informants in this study were pregnant women, mothers with infants and toddlers, the father of the babies and toddlers, community leaders, and local health officials. These results indicate that in general the role of midwife in the village of Bolo is divided into three periods role, namely a role in the pregnancy, labor and management role in postpartum care. Of the three traditional midwives in the village of Bolo is found that there is specialization and division of labor is not in writing, in which each midwife handles different issues. Can also be shown that in general the role of traditional birth attendants can be classified into two categories of functions, namely the function of maternal and child health care, outwardly and non-medical functions, namely as a mediator of patients with the supernatural world. Factors that cause birth attendants still play a role in society Bolo is due to economic factors, customs, traditions, understand Javanese science, psychological, suggestions community, stability factor of self, confidence and inexperience midwife.